Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 208288 by efronzo1 last updated on 10/Jun/24

Answered by A5T last updated on 10/Jun/24

8(8+x)=(2r)(2r+2R)=4r^2 +4rR  ⇒x=((r^2 +rR−16)/2)...(i)  (8+x)^2 =R^2 +(2r+R)^2 =2R^2 +4rR+4r^2   ⇒x=(√(2R^2 +4rR+4r^2 ))−8...(ii)  BC=(√(4r^2 −25))  (√(BC^2 +BE^2 ))=EC=(√(R^2 +R^2 ))=R(√2)  ⇒2R^2 =4r^2 −25+(3+x)^2   ⇒x=(√(2R^2 −4r^2 +25))−3...(iii)  ((r^2 +rR−16)/2)=(√(2R^2 +4rR+4r^2 ))−8=(√(2R^2 −4r^2 +25))−3  ⇒r=((√(34))/2);R=((3(√(34)))/2)⇒x=9

$$\mathrm{8}\left(\mathrm{8}+{x}\right)=\left(\mathrm{2}{r}\right)\left(\mathrm{2}{r}+\mathrm{2}{R}\right)=\mathrm{4}{r}^{\mathrm{2}} +\mathrm{4}{rR} \\ $$$$\Rightarrow{x}=\frac{{r}^{\mathrm{2}} +{rR}−\mathrm{16}}{\mathrm{2}}...\left({i}\right) \\ $$$$\left(\mathrm{8}+{x}\right)^{\mathrm{2}} ={R}^{\mathrm{2}} +\left(\mathrm{2}{r}+{R}\right)^{\mathrm{2}} =\mathrm{2}{R}^{\mathrm{2}} +\mathrm{4}{rR}+\mathrm{4}{r}^{\mathrm{2}} \\ $$$$\Rightarrow{x}=\sqrt{\mathrm{2}{R}^{\mathrm{2}} +\mathrm{4}{rR}+\mathrm{4}{r}^{\mathrm{2}} }−\mathrm{8}...\left({ii}\right) \\ $$$${BC}=\sqrt{\mathrm{4}{r}^{\mathrm{2}} −\mathrm{25}} \\ $$$$\sqrt{{BC}^{\mathrm{2}} +{BE}^{\mathrm{2}} }={EC}=\sqrt{{R}^{\mathrm{2}} +{R}^{\mathrm{2}} }={R}\sqrt{\mathrm{2}} \\ $$$$\Rightarrow\mathrm{2}{R}^{\mathrm{2}} =\mathrm{4}{r}^{\mathrm{2}} −\mathrm{25}+\left(\mathrm{3}+{x}\right)^{\mathrm{2}} \\ $$$$\Rightarrow{x}=\sqrt{\mathrm{2}{R}^{\mathrm{2}} −\mathrm{4}{r}^{\mathrm{2}} +\mathrm{25}}−\mathrm{3}...\left({iii}\right) \\ $$$$\frac{{r}^{\mathrm{2}} +{rR}−\mathrm{16}}{\mathrm{2}}=\sqrt{\mathrm{2}{R}^{\mathrm{2}} +\mathrm{4}{rR}+\mathrm{4}{r}^{\mathrm{2}} }−\mathrm{8}=\sqrt{\mathrm{2}{R}^{\mathrm{2}} −\mathrm{4}{r}^{\mathrm{2}} +\mathrm{25}}−\mathrm{3} \\ $$$$\Rightarrow{r}=\frac{\sqrt{\mathrm{34}}}{\mathrm{2}};{R}=\frac{\mathrm{3}\sqrt{\mathrm{34}}}{\mathrm{2}}\Rightarrow{x}=\mathrm{9} \\ $$

Answered by mr W last updated on 10/Jun/24

Commented by mr W last updated on 12/Jun/24

((x/2)/a)=(a/(x+3+5))   ⇒2a^2 =x(x+8)  (2b)^2 −5^2 =((√2)a)^2 −(x+3)^2   ⇒4b^2 =25+x(x+8)−(x+3)^2   ⇒2b^2 =8+x  ((2b)/5)=((x+3+5)/(a+2b))  ⇒5(x+8)=2ab+4b^2   ⇒5(x+8)=2ab+16+2x  ⇒2ab=3(x+8)  ⇒4a^2 b^2 =9(x+8)^2   ⇒x(x+8)(8+x)=9(x+8)^2   ⇒x=9 ✓

$$\frac{{x}/\mathrm{2}}{{a}}=\frac{{a}}{{x}+\mathrm{3}+\mathrm{5}}\: \\ $$$$\Rightarrow\mathrm{2}{a}^{\mathrm{2}} ={x}\left({x}+\mathrm{8}\right) \\ $$$$\left(\mathrm{2}{b}\right)^{\mathrm{2}} −\mathrm{5}^{\mathrm{2}} =\left(\sqrt{\mathrm{2}}{a}\right)^{\mathrm{2}} −\left({x}+\mathrm{3}\right)^{\mathrm{2}} \\ $$$$\Rightarrow\mathrm{4}{b}^{\mathrm{2}} =\mathrm{25}+{x}\left({x}+\mathrm{8}\right)−\left({x}+\mathrm{3}\right)^{\mathrm{2}} \\ $$$$\Rightarrow\mathrm{2}{b}^{\mathrm{2}} =\mathrm{8}+{x} \\ $$$$\frac{\mathrm{2}{b}}{\mathrm{5}}=\frac{{x}+\mathrm{3}+\mathrm{5}}{{a}+\mathrm{2}{b}} \\ $$$$\Rightarrow\mathrm{5}\left({x}+\mathrm{8}\right)=\mathrm{2}{ab}+\mathrm{4}{b}^{\mathrm{2}} \\ $$$$\Rightarrow\mathrm{5}\left({x}+\mathrm{8}\right)=\mathrm{2}{ab}+\mathrm{16}+\mathrm{2}{x} \\ $$$$\Rightarrow\mathrm{2}{ab}=\mathrm{3}\left({x}+\mathrm{8}\right) \\ $$$$\Rightarrow\mathrm{4}{a}^{\mathrm{2}} {b}^{\mathrm{2}} =\mathrm{9}\left({x}+\mathrm{8}\right)^{\mathrm{2}} \\ $$$$\Rightarrow{x}\left({x}+\mathrm{8}\right)\left(\mathrm{8}+{x}\right)=\mathrm{9}\left({x}+\mathrm{8}\right)^{\mathrm{2}} \\ $$$$\Rightarrow{x}=\mathrm{9}\:\checkmark \\ $$

Commented by Tawa11 last updated on 21/Jun/24

Nice sir.  I am learning questions like this.

$$\mathrm{Nice}\:\mathrm{sir}. \\ $$$$\mathrm{I}\:\mathrm{am}\:\mathrm{learning}\:\mathrm{questions}\:\mathrm{like}\:\mathrm{this}. \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com